2017
DOI: 10.1016/j.ajog.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Immediate postpartum levonorgestrel intrauterine device insertion and breast-feeding outcomes: a noninferiority randomized controlled trial

Abstract: BACKGROUND Immediate postpartum levonorgestrel intrauterine device insertion is increasing in frequency in the United States, but few studies have investigated the effect of early placement on breast-feeding outcomes. OBJECTIVE This study examined the effect of immediate vs delayed postpartum levonorgestrel intrauterine device insertion on breast-feeding outcomes. STUDY DESIGN We conducted this noninferiority randomized controlled trial at the University of Utah and the University of New Mexico Health Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…For the primary outcome of any breastfeeding at 8 weeks postpartum, postplacental insertion was noninferior to delayed insertion (79% vs. 84%, respectively, p= .28). Time to lactogenesis was also noninferior in the postplacental compared to delayed insertion groups (65.3 vs. 63.6 h, p=.61) [81]. Based on the results of this definitive study, we do not recommend withholding the option of postplacental LNG-IUD for breastfeeding women.…”
Section: Does Postplacental Iud Insertion Have Any Effect Onmentioning
confidence: 71%
“…For the primary outcome of any breastfeeding at 8 weeks postpartum, postplacental insertion was noninferior to delayed insertion (79% vs. 84%, respectively, p= .28). Time to lactogenesis was also noninferior in the postplacental compared to delayed insertion groups (65.3 vs. 63.6 h, p=.61) [81]. Based on the results of this definitive study, we do not recommend withholding the option of postplacental LNG-IUD for breastfeeding women.…”
Section: Does Postplacental Iud Insertion Have Any Effect Onmentioning
confidence: 71%
“…No other patient or insertion‐related variables were found to be significant in relation to expulsion risk. Some studies have suggested a higher expulsion rate for the intrauterine system compared with the copper intrauterine device, although the overall evidence is conflicting. Most women in our study received an intrauterine system and we found little evidence of a difference in expulsion rate between the two devices, although further research from larger comparative trials is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, postplacental placement at the time of caesarean section has lower expulsion rates than post-placental vaginal insertions. Insertion complications of perforation and infection are not increased by IUD placement at any time during the post-partum period [14,15,18].…”
Section: Discussionmentioning
confidence: 99%